2017
DOI: 10.1007/s00018-017-2517-x
|View full text |Cite
|
Sign up to set email alerts
|

Shaping the cellular landscape with Set2/SETD2 methylation

Abstract: Chromatin structure is a major barrier to gene transcription that must be disrupted and re-set during each round of transcription. Central to this process is the Set2/SETD2 methyltransferase that mediates co-transcriptional methylation to histone H3 at lysine 36 (H3K36me). Studies reveal that H3K36me not only prevents inappropriate transcriptional initiation from arising within gene bodies, but that it has other conserved functions that include the repair of damaged DNA and regulation of pre-mRNA splicing. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
108
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(119 citation statements)
references
References 173 publications
(249 reference statements)
4
108
0
Order By: Relevance
“…As shown in Figure 7, compared with control oocytes, SETD2 depletion resulted in a drastic reduction of H3K36 tri-methylation in metaphase chromosomes, implying that H3K36me3 may be a potential target mediating the action of SETD2 on oocytes. SETD2, as a writer of methylational modification, regulates the maintenance of chromatin structure and genome stability, ensuring normal cell viability (McDaniel & Strahl, 2017;Pfister et al, 2014;Zhang, Cooper, & Brockdorff, 2015). In the current study, we showed that depletion of SETD2 in oocytes resulted in an abnormal spindle morphology and chromosome disorganization (Figure 3).…”
Section: Decreased Methylation Level Of Histonesupporting
confidence: 49%
“…As shown in Figure 7, compared with control oocytes, SETD2 depletion resulted in a drastic reduction of H3K36 tri-methylation in metaphase chromosomes, implying that H3K36me3 may be a potential target mediating the action of SETD2 on oocytes. SETD2, as a writer of methylational modification, regulates the maintenance of chromatin structure and genome stability, ensuring normal cell viability (McDaniel & Strahl, 2017;Pfister et al, 2014;Zhang, Cooper, & Brockdorff, 2015). In the current study, we showed that depletion of SETD2 in oocytes resulted in an abnormal spindle morphology and chromosome disorganization (Figure 3).…”
Section: Decreased Methylation Level Of Histonesupporting
confidence: 49%
“…In addition, TOR inhibitors combined with SETD2 knockdown is a lethal combination to leukemic cells (Zhu et al, 2014), suggesting that SETD2 and its role in enforcing transcriptional fidelity is likely conserved and important to the growth of cancer cells. As SETD2 is found mutated in a variety of cancers (McDaniel and Strahl, 2017), it will be of significant interest to determine the degree to which transcriptional fidelity regulated by SETD2/H3K36me3 contributes to its role in cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…Set2 is a highly conserved histone methyltransferase that methylates histone H3 at lysine 36 (H3K36) (McDaniel and Strahl, 2017; Strahl et al, 2002; Venkatesh and Workman, 2015). In contrast to higher eukaryotes, Set2 is the sole H3K36 methyltransferase in Saccharomyces cerevisiae, and is responsible for modifying H3K36 with up to three methyl groups, creating mono-, di-, and tri-methylated H3K36.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HDAC1 and HDAC2, prominent members of the class I HDACs, are found in the repressive Sin3, NuRD, and CoREST complexes (Yang & Seto, 2008). Loss or inhibition of HDAC1/Rpd3 leads to increased histone acetylation, which in turn can lead to increased expression of target genes and cryptic transcripts (Carrozza et al, 2005;Joshi & Struhl, 2005;Li et al, 2007;Rando & Winston, 2012;Brocks et al, 2017;McDaniel & Strahl, 2017).…”
Section: Introductionmentioning
confidence: 99%